2009
DOI: 10.1016/j.annepidem.2008.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Survival in Ontario and California, 1998–2006: Socioeconomic Inequity Remains Much Greater in the United States

Abstract: This study re-examined the differential effect of socioeconomic status on the survival of women with breast cancer in Canada and the United States. Ontario and California cancer registries provided 1,913 cases from urban and rural places. Stage-adjusted cohorts (1998Stage-adjusted cohorts ( -2000 were followed until 2006. Socioeconomic data were taken from population censuses. SES-survival associations were observed in California, but not in Ontario, and Canadian survival advantages in low-income areas were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…In a series of studies examining the effect of socioeconomic status on cancer survival in Canada and the United States, two countries with higher survival than England, a significant advantage was found for deprived patients in Canada compared to deprived patients in the US, 12 even after adjusting for differences in stage at diagnosis. 13 These findings implicate systematic differences in access to health care between the two countries, in particular in health insurance coverage for the most deprived populations. It is also worthy of note that differences in cancer survival between black and white populations in the US 14 are wider than any difference in survival between socioeconomic 1,2 or ethnic 15 groups in England.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of studies examining the effect of socioeconomic status on cancer survival in Canada and the United States, two countries with higher survival than England, a significant advantage was found for deprived patients in Canada compared to deprived patients in the US, 12 even after adjusting for differences in stage at diagnosis. 13 These findings implicate systematic differences in access to health care between the two countries, in particular in health insurance coverage for the most deprived populations. It is also worthy of note that differences in cancer survival between black and white populations in the US 14 are wider than any difference in survival between socioeconomic 1,2 or ethnic 15 groups in England.…”
Section: Discussionmentioning
confidence: 99%
“…In Denmark, the publicly paid health care system is supposed to ensure equal access to health care services regardless of socioeconomic status or employment. However, social inequality in survival after cancer has been shown in several countries [24][25][26][27], including Denmark [28,29].…”
Section: Demographic and Socioeconomic Inequality?mentioning
confidence: 98%
“…Admittedly, our findings are most generalizable to such places. It should be noted, however, that after accounting for demographic, socioeconomic and clinical factors, place, per se, did not seem to matter in any of this study's analytic models nor in those of other of this field's studies (e.g., Gorey, in press;Gorey et al, 2009cGorey et al, , 2009d. Furthermore, though not as well controlled, this study's general pattern of findings had previously been observed in Manitoba and in a number of other states: Michigan, Washington, Connecticut, Iowa and Hawaii (Gorey et al, 1997(Gorey et al, , 2000a(Gorey et al, , 2000b(Gorey et al, , 2003.…”
Section: Potential Study Limitationsmentioning
confidence: 99%
“…Samples of 50 each, in extremely poor and extremely affluent, Canadian and American neighborhoods were thus required (α=0.05 [2-tailed] and power [1−β]=0.80; Fleiss, 1981). Finally, because previous research observed similar income-breast cancer care gradients in large and small urban areas, they were represented equally (Gorey et al, 2009c(Gorey et al, , 2009d). …”
Section: Extremely Poor and Extremely Affluent Neighborhoods-statisticsmentioning
confidence: 99%
See 1 more Smart Citation